Descent : a novel - Johnston, Tim, 1962- (Chapel Hill : Algonquin Books of Chapel Hill, 2015)
"Descent, the story of a family undone by the disappearance of a daughter who went out for a morning run and didn't come back, marks the adult fiction debut of a remarkable young writer. Stunning in its emotional impact, Descent is a compulsively readable page-turner with a strong literary sensibility." --
Includes A Note from the Author and Questions for Discussion.
Keywords: Missing persons -- Fiction; Abduction -- Fiction; Families -- Fiction; Loss (Psychology) -- Fiction; Rocky Mountains -- Fiction